2018
DOI: 10.3349/ymj.2018.59.10.1232
|View full text |Cite
|
Sign up to set email alerts
|

Single Ventilation during Cardiopulmonary Resuscitation Results in Better Neurological Outcomes in a Porcine Model of Cardiac Arrest

Abstract: PurposeRecent basic life support (BLS) guidelines recommend a 30:2 compression-to-ventilation ratio (CV2) or chest compression-only cardiopulmonary resuscitation (CC); however, there are inevitable risks of interruption of high-quality cardiopulmonary resuscitation (CPR) in CV2 and hypoxemia in CC. In this study, we compared the short-term outcomes among CC, CV2, and 30:1 CV ratio (CV1).Materials and MethodsIn total, 42 pigs were randomly assigned to CC, CV1, or CV2 groups. After induction of ventricular fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…However, there were more rib fractures in the CCC group in their study. Other prior research with animals has mainly focused on comparing shorter compression periods between ventilations, such as 15:1 and 15:2 [ 17 ] and compressions only in 30:1 and 30:2 protocols [ 13 ]. The longer compression phase seems to provide better haemodynamic parameters without major compromises in blood gas values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were more rib fractures in the CCC group in their study. Other prior research with animals has mainly focused on comparing shorter compression periods between ventilations, such as 15:1 and 15:2 [ 17 ] and compressions only in 30:1 and 30:2 protocols [ 13 ]. The longer compression phase seems to provide better haemodynamic parameters without major compromises in blood gas values.…”
Section: Discussionmentioning
confidence: 99%
“…A multiple comparison test was also run as a sensitivity analysis. The sample size was estimated based on arterial blood gas data from Kim et al [ 13 ]. According to this, a sample size of 30 divided into two equal groups would be sufficient to detect a 20 mmHg difference in PaO 2 with a statistical power of 0.95.…”
Section: Methodsmentioning
confidence: 99%
“…For the most critical outcome of favorable neurological outcome, we identified 28 studies including 1 clinical trial in adult human beings (low quality of evidence, downgraded for very serious indirectness), 70 10 experimental swine trials (very low quality of evidence, downgraded for serious risk of bias, serious indirectness, and serious inconsistency), 54,[71][72][73][74][75][76][77][78][79] and 17 observational studies in people (very low quality of evidence, downgraded for serious risk of bias, very serious indirectness, and serious inconsistency) [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] that addressed the PICO question. One randomized, multicenter clinical trial of adults with OHCPA receiving dispatcher-instructed bystander CPR found no difference in favorable neurologic outcome between compression-only CPR and conventional CPR.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…70 Four experimental swine studies, 2 of which were asphyxial arrest models, found that conventional CPR was superior for favorable neurologic outcome, 71,73,74,76 whereas 6 experimental swine studies found no difference between compression only CPR and conventional CPR. 54,73,75,[77][78][79] Five observational studies in people found conventional CPR was associated with a better neurologic outcome 85,86,89,91,96 when compared to compression-only CPR; however, 12 human clinical observational studies showed no difference in this outcome with compression-only CPR versus conventional CPR. [80][81][82][83][84]87,88,90,[92][93][94][95] For the next critical outcome of survival to discharge, we identified 3 clinical trials (low quality of evidence, downgraded for very serious indirectness) 70,97,98 and 5 observational studies (very low quality of evidence, downgraded for very serious indirectness and serious inconsistency) 83,[89][90][91]94 that addressed the PICO question.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…The application of new biomarkers that simply and accurately predict the development of poor neurological outcomes and mortality after post-resuscitation may improve the prognosis of patients by enabling innovative monitoring, early aggressive treatment, and therapeutic strategies. 5 6 Thrombotic microangiopathy (TMA) is characterized by three important elements including higher levels of lactate dehydrogenase, thrombocytopenia, and fragmented erythrocytes (schistocytes). 7 Several critical conditions lead to the development of systemic endothelial injury in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%